Acupuncture for Postoperative Neuropathic Pain: A Case Report - Deity Nugraha; Elies Fitriani; Adiningsih Srilestari (Bali Medical and Wellness Journal, 2024)
Introduction: Postoperative neuropathy can result from nerve transection, bruising, stretching, or inflammation. Chronic Post-Surgical Neuropathic Pain (CPSNP) refers to pain persisting for at least three months after surgery, distinct from preoperative pain and localized to the surgical site or referral area. Acupuncture, a therapeutic technique for acute and chronic pain, has shown promise in managing CPSNP. In this case report, we explore the use of acupuncture to alleviate chronic pain following hand surgery. CPSNP poses significant challenges for patients recovering from surgical procedures. Acupuncture, with its potential to modulate nerve activity and activate pain control systems in the brain, offers an alternative approach to pain management. Case Report: Patient Profile: A 37-year-old woman presented to the medical acupuncture polyclinic with complaints related to her left hand. Specifically, she experienced numbness, heat, and pain in the tips of fingers 2, 3, 4, and 5. Occasionally, the discomfort extended to her elbow. Medical History: The patient had undergone Carpal Tunnel Syndrome (CTS) surgery on her left hand approximately one year ago. The diagnosis of CTS was established in 2021, leading to open surgery on the wrist. Current Pain Assessment: The patient reported a Numeric Rating Scale (NRS) pain score of 5. Physical Examination: Examination revealed pain and limited range of motion (ROM) in her hand. Acupuncture Treatment: Manual acupuncture therapy was administered, targeting specific body acupuncture points and utilizing ear acupuncture. Outcome: After six therapy sessions, the patient experienced a reduction in pain intensity and an improvement in overall quality of life. Conclusion: Acupuncture shows promise as an adjunctive therapy for managing chronic post-surgical neuropathic pain. Further research is warranted to explore its efficacy and long-term effects in similar cases.